3D Finite Element Analysis of PWA-Oil Sand Terrain System Interaction. (17th May 2012) - Li, Y.; Frimpong, S.; Liu, W. Y.
Abstract : A simulator for analyzing the interaction between the oil sand terrain and a pipe wagon articulating (PWA) system has been developed in this paper. An elastic-plastic oil sand model was built based on the finite element analysis (FEA) method and von Mises yield criterion using the Algor mechanical event simulation (MES) software. The three-dimensional (3D) distribution of the stress, strain, nodal displacement, and deformed shape of the oil sands was animated at an environmental temperature of 25°C. The 3D behavior of the oil sand terrain was investigated with different loading conditions. The effect of the load and contact area on the stress and nodal displacement was analyzed, respectively. The results indicate that both the max stress and max nodal displacement increase with the load varying from 0 to3.6 E + 7 N and decrease with the contact area varying from 2 to 10 m 2 . The method presented in this paper forms the basis for evaluating the bearing capacity of oil sand ground.